Perubahan Uang Inti dan Penawaran Uang - Didik Susetyo; Rina Consela (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2011)
The purpose of this research is to know how the impact of exchange base money on money supply. The term of base money in this research is debt of monetary authority to citizen and financial institutional which influenced by net claims on government, net claims on private sector and net foreign assets. In this research, used data is secondary data which source from Bank Indonesia, Statistic Center Board, and others of journals and books. This research was done by using multi-regression linear method. The result showed that increased base money improved money supply significantly. The exchange of base money would influence positive effect on money supply.Keywords: Base money, money supply